Genetic Characterization of Quercus suber L.: 1. Preliminary Detection of Histone Promoter Variabilities - Brás,David (2001)
The genetic variability of Quercus suber L. has been verified and examined by several authors, mainly through the evaluation of the restriction fragment length polymorphisms (RFLPs), isoenzymatic polymorphisms, suberin and waxes compositions, and, also, suberins triglyceride contents in order its potential use in the improvement of the cork quality could be established. In this context, total DNA extracts obtained from two Portuguese cork oaks have been amplified by the polymerase chain reaction (PCR), using a specific, well-conserved molecular marker that occurs in the proximal promoter region of the plant histone H3 genes (type I element, CCACGTCACCGATCCGCG). A comparison of the electrophoretic profiles of the PCR products has allowed the detection of genetic variabilities between the studied trees whose potential implications may be associated with the cork quality. These results, that are here reported for the first time as far as known, although preliminary suggest that, at least, the molecular marker above mentioned may be used for screening, and characterization of the Quercus suber L. genetic variabilities. This is the objective of several studies that are actually in course by this team.